A Review of Febrile Seizures: Recent Advances in Understanding of Febrile Seizure Pathophysiology and Commonly Implicated Viral Triggers - Sawires, Rana; Buttery, Jim; Fahey, Michael (Frontiers in Pediatrics, 2022)
Febrile seizures are one of the commonest presentations in young children, with a 2-5% incidence in Western countries. Though they are generally benign, with rare long-term sequelae, there is much to be learned about their pathophysiology and risk factors. Febrile seizures are propagated by a variety of genetic and environmental factors, including viruses and vaccines. These factors must be taken into consideration by a clinician aiming to assess, diagnose and treat a child presenting with fevers and seizures, as well as to explain the sequelae of the febrile seizures to the concerned parents of the child. Our article provides an overview of this common childhood condition, outlining both the underlying mechanisms and the appropriate clinical approach to a child presenting with febrile seizures.